Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.3389/fmicb.2015.00951
|View full text |Cite
|
Sign up to set email alerts
|

Cooperative pathogenicity in cystic fibrosis: Stenotrophomonas maltophilia modulates Pseudomonas aeruginosa virulence in mixed biofilm

Abstract: The present study was undertaken in order to understand more about the interaction occurring between S. maltophilia and P. aeruginosa, which are frequently co-isolated from CF airways. For this purpose, S. maltophilia RR7 and P. aeruginosa RR8 strains, co-isolated from the lung of a chronically infected CF patient during a pulmonary exacerbation episode, were evaluated for reciprocal effect during planktonic growth, adhesion and biofilm formation onto both polystyrene and CF bronchial cell monolayer, motility,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
80
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(96 citation statements)
references
References 62 publications
7
80
3
Order By: Relevance
“…The results from CI versus RIR suggested that I. limosus and S. maltophilia are, in a general point of view, outcompeted. These findings are in agreement with Pompilio et al (2015) that found that P. aeruginosa , in dual biofilms, significantly affect S. maltophilia growth. They also shown that, when grown with S. maltophilia in dual biofilms, some P. aeruginosa virulence factors, as alkaline protease and alginate, were up-regulated.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The results from CI versus RIR suggested that I. limosus and S. maltophilia are, in a general point of view, outcompeted. These findings are in agreement with Pompilio et al (2015) that found that P. aeruginosa , in dual biofilms, significantly affect S. maltophilia growth. They also shown that, when grown with S. maltophilia in dual biofilms, some P. aeruginosa virulence factors, as alkaline protease and alginate, were up-regulated.…”
Section: Discussionsupporting
confidence: 93%
“…Data suggest a potential protective effect of P. aeruginosa over the other species against ciprofloxacin. Similar hints were pointed out by Pompilio et al (2015) as they stated that P. aeruginosa might be responsible for the protection of S. maltophilia against tobramycin in dual biofilms due to alginate overproducing. Moreover, data also shown that, independently of the reduced biomass noticed in P. aeruginosa + S. aureus and P. aeruginosa + I. limosus dual biofilms, the high number of biofilm-encased cells was enough to imply an increased tolerance on those consortia.…”
Section: Discussionsupporting
confidence: 72%
“…Dominantly in cystic fibrosis several studies focused on interaction of P. aeruginosa with other bacterial species, but only a few have been published on the interaction between P. aeruginosa and S. maltophilia. It was found that S. maltophilia increases the risk of resistance of P. aeruginosa to polymyxin; beta-lactamase leaking from S. maltophilia enhances the growth of P. aeruginosa in the presence of beta-lactam antibiotic agents; S. maltophilia might confer a selective fitness advantage to P. aeruginosa and increase the virulence of P. aeruginosa (18). The interaction of A. baumannii and S. maltophilia is not discussed in the literature, except for their ability to increase each other's biofilm production (19).…”
Section: Discussionmentioning
confidence: 99%
“…Pseudomonas aeruginosa the major pathogen in the CF lung due to biofilm-growing mucoid (alginate-producing) strains, which confer resistance to the host defense mechanism. Pompilio et al [36] reported the prevalence of P . aeruginosa in mixed biofilm communities formed by P .…”
Section: Discussionmentioning
confidence: 99%